The Interpretation Of Tropical Architecture in Designing Business Hotel In Medan - Great Manganju Purba; Morida Siagian (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
The increasing level of urbanization is in line with the need for housing. Not only that, but also the increase in people's need for a place to live has led to an increase in land prices. The city of Medan is one of the developing cities that many people pay attention to. The development of this city has attracted many people's attention, making young investors and young business people who are part of the community who have a contemporary and instant lifestyle and lifestyle, so that the need for lodging places becomes a priority. And due to the increase in the value of existing land in the city of Medan, lodging buildings that have good land efficiency are needed, such as mid-rise and high-rise buildings. Nowadays, hotels are not just a place to stay anymore for visitors doing business or tourism. But over the times, hotels are currently used to accommodate weddings, meetings, parties, and are often also used as recreational or entertainment facilities for the community. Seeing the small number of four-star hotels in Medan City, especially in Polonia District, is the reason why additional four-star hotel buildings are needed. Therefore, from these problems, the authors feel compelled to play a role in implementing ideas, ideas, and knowledge about four-star hotels, by designing business hotels with four-star facilities using a tropical architectural approach.